Pengaruh Infrastruktur dan Pendidikan Terhadap Pertumbuhan Ekonomi di Kabupaten Sidoarjo (Jurnal Riset Manajemen dan Akuntansi, 2025)
Economic Growth in Sidoarjo Regency is a government concern to create a prosperous society. This causes the need to analyze the factors that influence Economic Growth in Sidoarjo Regency. This study aims to analyze the condition of infrastructure and education in Sidoarjo Regency, analyze the development of economic development in Sidoarjo Regency and analyze the influence of infrastructure and education on economic development in Sidoarjo Regency. This type of research is quantitative research. The study uses secondary data on infrastructure, education and economic development data. Data collection techniques through documentation methods and analyzed through SPSS multiple linear regression analysis. The results of the study prove that the condition of Infrastructure in Sidoarjo Regency has developed significantly, which is proven by the absence of households that do not have electricity infrastructure to meet their living needs and the Education factor has developed where more and more people are going to school to a higher level. Then the Development of Economic Development in Sidoarjo Regency has increased every year which can be proven from the Gross Regional Domestic Product (GRDP) value. Simultaneously, the Infrastructure and Education variables have a significant effect on economic growth in Sidoarjo Regency. Meanwhile, partially, the infrastructure variable has a negative and significant influence on economic growth and the education variable has a positive but not statistically significant influence on economic growth